Job Training Information System at the Sidoarjo Regency Manpower Office - M. Arif Mansur; Nuril Lutvi Azizah (CV. Media Digital Publikasi Indonesia, 2025)
The use of information technology at the Sidoarjo Regency Manpower Office has had a positive impact on job training services. Computerized systems are currently the most important part of advances in information technology. Therefore, the author wishes to develop a computer system that can facilitate the work of the Sidoarjo Regency Manpower Office in meeting the needs of the Manpower Office and the community regarding the job training system in the city of Sidoarjo. The objective of this job training information system is to eliminate the need for people to come to the Manpower Office to manually register for training in the Sidoarjo area. The techniques used in this application are the waterfall method and the CodeIgniter framework.